Incidence and contributing factors for uterine rupture in patients undergoing second trimester termination of pregnancy in a large tertiary hospital - a 10-year case series. (August 2018) - Daniel Seow Choon, Koh; Eek Chaw, Tan; Hester Chang Qi, Qi Lau; Mor Jack, NG; Wan Shi, Tay; Kok Hian, Tan
Abstract: Introduction: Uterine rupture is a rare complication in second trimester termination of pregnancy (TOP) with an overall incidence of up to 1.1%. There are concerns that patients with previous caesarean section(s) were at an increased risk of uterine rupture. However, there is no published data in our local population to date. This study aims to identify the incidence and contributing factors for uterine rupture in women undergoing TOP in Singapore. Study Design: This is a retrospective review of all women who had TOP between 14 +0 weeks to 23 +6 weeks gestation from January 2005 to December 2014 in a large tertiary hospital. Patients' characteristics and details of TOP were retrieved from pre-existing hospital databases. The gestation age and dose of gemeprost used were retrieved from an internal hospital audit conducted from December 2012 to July 2016. Results: A total of 3385 patients underwent TOP from 2005 to 2014. An estimated 339 patients had a scarred uterus. Seven cases of uterine rupture were identified, with an overall incidence of 0.21% (7/3385). The incidence of uterine rupture in patients with scarred uterus was 2.1% (7/339). Contributing factors identified included higher mean dose of abortifacient, usage of multiple abortifacients and methods, advanced gestation age and short interval between last caesarean section and current TOP. Conclusion: Second trimester TOP on scarred uterus warrants careful usage of abortifacient with minimal cumulative dosage and should be carried out in early second trimester gestation whenever feasible. Prostaglandin analogues appeared to be safe for TOP in unscarred uteruses.